COMPARATIVE STUDY BETWEEN GOOGLE TRANSLATE AND PRINTED DICTIONARY TO INCREASE STUDENTS’ VOCABULARY - Indrawati, Inda; Hidayati, Hidayati; Marzuki, Marzuki; Tiara, Tiara (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study compares the effectiveness of Google Translate and printed dictionaries in enhancing students' vocabulary acquisition. A quantitative, quasi-experimental design was employed. Participants were twenty eighth-grade students from SMPN 4 Tolitoli (2023/2024), Central Sulawesi, Indonesia, divided into a control group (using printed dictionaries) and a treatment group (using Google Translate). Pre-tests and post-tests, consisting of multiple-choice, matching, and fill-in-the-blank tasks, assessed vocabulary knowledge. Data collection involved pre-tests, a four-week treatment, and post-tests. Descriptive statistics and t-tests analyzed the data. Both groups showed improved vocabulary acquisition post-treatment, with no significant differences in learning outcomes. Despite similar average scores, substantial variability was observed within each group, reflected by high standard deviations and wide score ranges. These results suggest both tools have unique strengths: Google Translate offers convenience and accessibility, while printed dictionaries provide comprehensive definitions and contextual understanding. A blended approach incorporating both tools is recommended for educators and curriculum designers. Future research should explore long-term vocabulary retention and the integration of digital tools into traditional learning frameworks, considering personalized strategies to address diverse student needs.